The Contextual Problem-Based Learning Model Enhances Problem-Solving Abilities and Science Process Skills Among Elementary School Students - Kadek Hengki Primayana; Putu Yulia Angga Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
Science learning in elementary schools often emphasizes the theoretical delivery of concepts, which has not optimally fostered students’ critical thinking and scientific skills. This study aims to analyze the effect of contextual Problem-Based Learning on elementary school students’ problem-solving abilities and scientific process skills in science learning. This study employed a quantitative approach with a quasi-experimental design, as full randomization of classes was not feasible in the natural school setting. The research participants consisted of fifth-grade students from two public elementary schools, which were assigned as the experimental and control groups. Data were collected through problem-solving ability tests and scientific process skills tests. The data were analyzed using the Analysis of Covariance to control for differences in students’ initial abilities. The results indicate that contextual problem-based learning exerts a very strong effect on improving students’ problem-solving abilities after controlling for their initial competence. In addition, this learning model also has a significant effect on students’ scientific process skills, with a moderate level of influence. These findings suggest that contextual problem-based learning is effective for elementary school science instruction, as it enhances higher-order thinking skills while simultaneously fostering students’ scientific skills in a more optimal and sustainable manner.